Clinical and laboratory diagnosis of rare coagulation disorders (RCDs). Issue 196 (December 2020) - Menegatti, Marzia; Palla, Roberta
Abstract: Rare coagulation disorders (RCDs) are a group of diseases due to coagulation factors deficiency leading to life-long bleeding diathesis. The diagnosis of RCDs is challenging due to the limited knowledge of these disorders and the large heterogeneity of their bleeding patterns. The clinical symptoms of RCDs are extremely diverse in terms of bleeding type, site, severity, age at onset, and duration. The strength of the association between clotting factor activity level in plasma and clinical symptoms is also variable within each RCD. The clinical evaluation of RCDs starts with a detailed collection of clinical history and has been facilitated by bleeding assessment tools, however their effectiveness in diagnosing RCDs requires further investigation. The following laboratory diagnosis of RCDs involves coagulation screening tests, including activated partial thromboplastin time, prothrombin time, and thrombin time. After ruling out the presence of an inhibitor by mixing studies, in case of abnormal results, the specific deficiency is identified by performing one-stage clotting assays using the specific factor-depleted plasmas as substrate. In fibrinogen and FXIII deficiencies coagulation screening tests are not informative, therefore additional tests are needed. Global assays have been developed and are thought to aid in patient management, however, they are not well standardized yet. In addition to outlining the principles of clinical and laboratory diagnosis, this review explores molecular basis of RCDs and laboratory techniques for genetic analysis, and discusses the importance and effectiveness of quality control programs to ensure standardized laboratory results. Highlights: Rare coagulation diseases (RCDs) are inherited deficiencies of coagulation factors. The clinical picture of RCDs is characterized by heterogeneous bleeding diathesis. Bleeding assessment tools were developed to aid in the clinical diagnosis. Screening clotting tests and global assays identify the specific factor deficiency. Molecular diagnosis is based on the identification of causative genetic variants.